(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2020)
Nowadays, it is a norm for patients to claim for medical negligence. Negligence includes the offence of giving a wrong diagnosis, mistreatment and failure to do treatment which resulting in patients getting disability or death. The objectives of the article are to discuss the efforts made to prevent the occurrence of medical misconduct, and the law that protects victims of medical misconduct. This article is based on qualitative research and using a comparative socio-legal method. The research uses a variety of data collection methods i.e. library search, documentation review, observation, interviews and questionnaires. Data were analyzed by content analysis and t-test. The result shows there are five parameters that have the sig <0.05 significant legal protection for victims of wrongdoing which is better in Malaysia rather than in Indonesia. In Indonesia, negligence is specified in the Penal Code, Sections 359 and 360, and the Law Number 29, Section 1365 and 1239, while in Malaysia are stated in the law of tort. Legal protections for victims of wrongdoings in Indonesia are still not effective even though there is a law Number 29 of 2004 because it was not in favour of the patients, but it is more favourable to medical practitioner. Keywords: comparison, law, Indonesia, Malaysia, misconduct, medical practitioners, negligence